Tools, resources and databases for SNPs and indels in sequences: a review. (1st January 2014) - Seal, Abhik; Gupta, Arun; Mahalaxmi, M.; Aykkal, Riju; Singh, Tiratha Raj; Arunachalam, Vadivel
Single Nucleotide Polymorphism (SNP) is a mutation where, a single base in the DNA differs from the usual base at that position. SNPs are the marker of choice in genetic analysis and also useful in locating genes associated with diseases. SNPs are important and frequently occurring point mutations in genomes and have many practical implications. In silico methods are easy to study the SNPs that are occurring in known genomes or sequences of a species of interest during the post genomic era. There are many on-line and stand alone tools to analyse the SNPs. We intend to guide the reader with the software details such as algorithmic background, file requirements, operating system specificity and species specificity, if any, for the tools of SNPs detection in plants and animals. We also list many databases and resources available today to describe SNPs in wide range of organisms.